First records of Calidris canutus Linnaeus, 1758 (Charadriiformes, Scolopacidae) and Trogon surrucura Vieillot, 1817 (Trogoniformes, Trogonidae) for Entre Ríos province (Argentina), and noteworthy reports of other birds in protected areas - Sarquis, Juan Andrés (2017)
We recorded 2 new bird species in Entre Ríos province, Argentina: Calidris canutus (Linnaeus, 1758) and Trogon surrucura Vieillot, 1817. In addition, we present 25 noteworthy records for bird species in El Palmar National Park, Pre Delta National Park, and other parts of the province.